Analisis Peran Ekonomi Kreatif Dalam Meningkatkan Pendapatan Pengrajin Dan Pengembangan Usaha Perspektif Ekonomi Islam (Studi Kasus : Pengrajin Toto Jaya Bingkai Di Kecamatan Medan Area) - Reni Hermila Hasibuan; Muhammad Arif; Atika Atika (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to (1) determine the role of the creative economy in increasing the income of Toto Jaya Frame craftsmen (2) determine the role of the creative economy in increasing business development for Toto Jaya Frame craftsmen (3) determine the role of the creative economy in increasing the income of craftsmen and business development of Toto Jaya Frame according to the perspective of Islamic economics. The method used in this study is a qualitative method with a descriptive approach. The data obtained in this study are in the form of primary data and secondary data. The data collection techniques used are through interviews, observation and documentation. The results of this study indicate that: (1) after the existence of Toto Jaya Frames in Kotamatsum II Village, Medan Area Regency, it can be seen that as many as 6 craftsmen have experienced an increase in income in 2020-2021 and already have a steady income (2) Toto Jaya Frames can also provide a role in an effort to develop the Toto Jaya Frame craftsman business by implementing several efforts/strategies, namely production, price, location and distribution, and promotion. From the several strategies that have been implemented, it is expected to be able to increase production levels and increase the income of craftsmen. (3) As well as in managing their business, Toto Jaya Frame craftsmen have also applied the principles of Islamic Economics such as the principle of divinity/monotheism, the principle of justice, the principle of responsibility and the principle of truth so that it does not harm either party.